Accumulation of education and regional income growth: Limited human capital effects in Norway - Hildegunn Stokke; Jørn Rattsø (European Regional Science Association (ERSA), 2011)
Accumulation of education and geographic concentration of educated people in cities are expected to generate urban income growth. New economic geography predicts income divergence across regions. We investigate the dynamic process of accumulating tertiary education and regional income growth in Norway during the past four decades. The expansion of smart cities goes along with catching up of education level in the periphery and overall the education levels converge. Income levels also are shown to converge in distribution analysis using Kernel functions and first order Markov chains. However, the movements in the income distribution are unrelated to the accumulation of education. The hypothesis of equal income transition probabilities across subgroups of regions with different increases in education cannot be rejected. We conclude that accumulation of education has not been important for the pattern of income growth. Catching up from low income is not driven by education and income growth has not taken off in cities with increasing education level.
Keywords: 330